An unfused-ring acceptor with high side-chain economy enabling 11.17% as-cast organic solar cells. Issue 3 (4th January 2021) - Du, Fuqiang; Wang, Hongtao; Zhang, Zhuohan; Yang, Linqiang; Cao, Jinru; Yu, Jiangsheng; Tang, Weihua
Abstract : Dibenzo[ c, g ]carbazole cored unfused-ring acceptor (DCB-4F) is designed with low weight ratio of side chains. Its as-cast OSCs with PM6 deliver 9.56% PCE with a V OC of 1.00 V. By adding 10 wt% PC71 BM, 11.17% PCE is readily achieved. The blends show homogeneous nano-fibrous morphology. Abstract : Side-chain engineering on nonfullerene acceptors (NFAs) is crucial for modulating their solubility and crystallinity as well as packing behaviours in active layers to pursue high-performance organic solar cells (OSCs). High weight ratios of side chains are generally used by NFAs for the desired device efficiencies. Side-chain economy has seldom been discussed despite increased cost and difficulties in synthesis when optimizing the molecular design. Herein, we introduce 7 H -dibenzo[ c, g ]carbazole (DCB) as an electron-donating core to design unfused-ring acceptors (UFAs) with a dramatically low weight ratio of side chains. DCB-4F has thus been designed and compared with the carbazole cored analogue (CB-4F). The unique conformation of the DCB core endows DCB-4F with higher solubility (8.2 mg mL −1 in chloroform) compared to CB-4F (2.2 mg mL −1 ) when using the same side chains. Featuring a lowest unoccupied molecular orbital (LUMO) level of −3.86 eV and an optical bandgap of 1.55 eV, the DCB-4F film exhibits an absorption profile (maximum 667 nm) complementary to polymer donor PM6. The PM6:DCB-4F as-cast OSCs deliver a power conversion efficiency (PCE) of 9.56% with a high open-circuit voltage ( V OC ) of 1.00 V. By adding 10 wt% PC71 BM into the casting solutions, a greatly improved PCE of 11.17% is readily achieved, which is one of the highest PCEs for as-cast single-junction UFA-based devices. The PM6:DCB-4F based blends show homogeneous nano-fiberous morphology and higher hydrophobicity. The design of conformation-tuned NFAs using sterically hindered DCB-like cores is promising to achieve highly efficient as-cast OSCs.